Suppression of material transfer at contacting surfaces: the effect of adsorbates on Al/TiN and Cu/diamond interfaces from first-principles calculations. (16th February 2018) - Feldbauer, Gregor; Wolloch, Michael; Bedolla, Pedro O; Redinger, Josef; Vernes, András; Mohn, Peter
Abstract: The effect of monolayers of oxygen (O) and hydrogen (H) on the possibility of material transfer at aluminium/titanium nitride (Al/TiN) and copper/diamond (Cu/Cdia ) interfaces, respectively, were investigated within the framework of density functional theory (DFT). To this end the approach, contact, and subsequent separation of two atomically flat surfaces consisting of the aforementioned pairs of materials were simulated. These calculations were performed for the clean as well as oxygenated and hydrogenated Al and Cdia surfaces, respectively. Various contact configurations were considered by studying several lateral arrangements of the involved surfaces at the interface. Material transfer is typically possible at interfaces between the investigated clean surfaces; however, the addition of O to the Al and H to the Cdia surfaces was found to hinder material transfer. This passivation occurs because of a significant reduction of the adhesion energy at the examined interfaces, which can be explained by the distinct bonding situations.